Organization of Islamic Co-operation (OIC) and Prospects of Yemeni Conflict Resolution: Delusion or Plausible Reality - M. Ihsan Qadir; M. Saifur Rehman (Journal of Political Studies, 2015)
The Romans named Yemen ‘An Arabian Flex’ (Happy Arabia) because of its blossoming rain-fed mountain scenery but the epithet sounds tragically extraneous today. Internal power struggle between various ethno-religious groups and tribes has destabilized the state. This tumultuous situation afforded political and physical space to non-state actors for gaining foot-hold and conducting terrorist activities within and without with impunity. Export of terrorism in the world in general and neighboring states, especially in Kingdom of Saudi Arabia, in particular, has long term political, social and economic implications for the region. Iran is blamed to be patronizing few terror outfits on sectarian grounds thus adding another dimension to regional instability. Military action initiated by coalition of GCC countries (spearheaded by Saudi Arabia) against sovereign state of Yemen is yet another test for OIC being an inter-governmental organization for resolution of conflicts in Muslim world. This article argues that illusive efforts undertaken by OIC so far in resolving this intra-Muslim world conflict are apocryphal and may pose serious threat to the wanting organization. There is a dire need for adopting a multipronged strategy by OIC for ensuring peace in Arab peninsula as blood never washes the blood.